REFORMASI MANAJEMEN PENDIDIKAN DI ERA 4.0: ANTARA ADAPTASI TEKNOLOGI DAN PENINGKATAN KUALITAS SDM - Raihanah; Khuzaini; Syahrial Shaddiq (PT. Hasba Edukasi Mandiri, 2025)
The transformation of education in the era of the Fourth Industrial Revolution has necessitated a reform in education management that is both adaptive and responsive to technological advancements. This study aims to examine the integration of technological adaptation and human resource development within the context of education management reform. The research employs a qualitative descriptive method through relevant literature studies. The findings indicate that the implementation of technologies such as Learning Management Systems (LMS), Artificial Intelligence (AI), and cloud computing offers significant opportunities for modernizing education management. However, the success of these technologies heavily depends on the competence and readiness of human resources. Therefore, capacity building through training and digital competency development is crucial. This study concludes that the synergy between technology and human capital is a fundamental pillar of digital-based education management reform. The implications of this research provide strategic direction for policymakers in developing sustainable future-oriented education policies.